Bezafibrate-driven mitochondrial targeting enhances antitumor immunity and prevents lung cancer via CD8+ T cell infiltration and MDSC reduction - Pan, Jing; Li, Jiaheng; Zhang, Qi; Huang, Mofei; Wang, Yian; You, Ming (Frontiers in Immunology, 2025)
Bezafibrate (BEZ) is a drug used to treat hypertriglyceridemia and its long-term use has been associated with reduced risk of cancer in patients with coronary artery disease. Recent studies uncovered that BEZ is a potent modulator of mitochondrial biogenesis through activation of PGC-1α/PPAR complexes, resulting in modulation of lipid metabolism and fatty acid oxidation. Mitochondria impact virtually all processes linked to oncogenesis, and disruption of normal mitochondrial bioenergetics and oxidative phosphorylation (OXPHOS) occurs early during oncogenesis to change the energy metabolism of cancer cells as well as various cells in the tumor microenvironment (TME). Therefore, we synthesized a BEZ analog (Mito-BEZ) that preferentially localizes to mitochondria, thereby enabling lower doses of Mito-BEZ than BEZ to achieve greater efficacy. Our studies demonstrate that Mito-BEZ is significantly more potent than BEZ at inhibiting LUAD cell growth in vitro and inhibiting lung tumorigenesis in preclinical mouse models. Mito-BEZ was also >200-fold more potent than BEZ at inhibiting both complex I and III in LUAD cells. Furthermore, Mito-BEZ suppresses oxidative metabolism in cancer cells while markedly upregulating mitochondrial function in effector CD8+ T cells, resulting in activation of a potent T cell immune response in the TME. Our results show that Mito-BEZ, with its favorable toxicity profile, exhibited a striking inhibitory effect on lung cancer progression and metastasis by targeting a fundamental difference in metabolic plasticity between cancer cells and effector T cells in the TME.